PENINGKATAN KETERAMPILAN MENULIS KARANGAN BERDASARKAN KEHIDUPAN DIRI SENDIRI DALAM CERPEN DENGAN MODEL QUANTUM TEACHING PADA SISWA KELAS X B SMA NEGERI 1 GIRIMULYO KULON PROGO TAHUN PELAJARAN 2013/2014 - Amalia Oktaviyani Fika Mulyana; Wijaya Heru Santosa (CARAKA, 2014)
This research is Classroom Action Research (CAR) about essay writing skills on a short story. The objective of this research was improving essay writing skill based on personal experience on a short story using Quantum Teaching Model at class X B students of  SMA  Negeri  1  Girimulyo  Kulon  Progo.  The research procedure includes cycle I with once meeting and cycle II with once meeting. The Quantum Teaching Model implementation using TANDUR framework can improve creativity and independent of students’ learning. The average score that was reached before action research process was 57,14. At the end of the cycle I the average score reached 70,28, so the increased score was 13,14. The end of cycle II score reached 79,19 so the increased score was 8,91 from cycle 1 and fulfill Minimum Completeness Criteria (KKM), that is 75.